MOBILE GROCERY: URBAN FOOD WAYS AND URBANIZATION - Khampa, Tanyawat; Sirasoonthorn, Patcharin; Photikanit, Kammales (PEOPLE: International Journal of Social Sciences, 2017)
The paper aims to consider relationship between urban food ways and Mobile Grocery. By investigate literature review and critical thinking to analyze relationships. There are four major groups of literature were reviewed, there were; 1) Sociology group by studying Mobile Grocery as part of the product from social structure. 2) Economics group by considering Mobile Grocery as a new way of demand and supply balancing in order to reflect the new form of consuming or market. 3) Culture groups by recognizing Mobile Grocery as part of the way of urban food 4) Public health group by concerning a mobile grocery as a part of health care problem which needed to be treat both of technical Health Sciences and policy perspectives. In health care perspective, the prevention of chronic disease by strengthening healthy lifestyles had been highlighted. Conversely, in the food arena, the prevention of chronic disease by focusing on obesity resolution. Unfortunately, the public health aspect was limited in Thai’s law. The standard of clean food remained mystery and the regulations for controlling mobile grocery have been legislated but not yet effective.